Profile of Critical Thinking Skills of Grade IV Elementary School Students on Energy Source Material - Fitanti, Sinta Yuni; Prahani, Binar Kurnia; Suryanti, Suryanti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study measured how well students can apply critical thinking skills when studying energy source materials in Natural Knowledge Science. In addition, research also reveals the factors that support or hinder the development of participants' critical thinking skills in the context of learning. i The research method used is descriptive qualitative with a survey approach. The research subject is 40 participants enrolled in the IV Grade of SDN Tanggul, Wonoayu District, Sidoarjo Regency, with an institution in the form of a written thesis and an interview with the IV Grade’s teachers of SDN Tanggul. Data analysis uses data reduction, data presentation, and conclusions drawn. The study results showed that, in general, the participants' ability to think critically. Interpretation indicators and analysis show more than good results compared to indicators of inference and evaluation. This indicates that the participants still have difficulties concluding and giving strong reasons to overcome their answers. The study's results also show that efforts to improve participants' critical thinking skills in the IV SDN Tanggul have been carried out but are still limited to conventional learning methods. This research suggests that teachers can use more interactive learning media and varied learning methods in learning science, especially energy source materials. In addition, teachers also need to provide trigger questions so that students can hone critical thinking skills and analyze information in depth. Thus, it is hoped that the ability of the participants to think critically will be improved so that they can face challenges in an increasingly complex era.